Determination of basic rock depth using Marquardt inversion based on schlumberger configuration geolistric resistivity data in Kampung Manggis village, Padang Panjang Barat - Herawati Herawati (Department of Physics – Universitas Negeri Padang UNP, 2014)
The purpose of this basic research are to describe the resistivity and the depth of basement rocks in Kampung Manggis Padang Panjang Barat. The depth of basement rocks are important to anticipate the landslide in the research area. This research use the exploration methods. The measurement use resistivity geoelectrical method with Schlumberger configuration. The techniques of analysis data use Marquardt inversion with initial damping factor 0,1 and minimum damping factor 0,001. The analysis of the data generating 2D cross section below the earth surface. The interpretation of the data generating the depth and the types of basement rocks. The result of this research show the type of basement rocks in Kampung Manggis Padang Panjang Barat is an igneous rock groups, namely Andesite. The resistivity of this andesite is 170,1–1658 Ωm. The depth of basement rocks below the earth surface varies, which generally more than 8 m deepness around Kampung Manggis Padang Panjang Barat area